Simplified multibody method for computing the modal characteristics of high-speed railway catenary - GONG Yongzhe; YANG Caijin; ZHAO Yu; LIU Kaizhong (机车电传动)
To simplify the computing process for the structural vibration modal properties of railway catenary based on absolute nodal coordinates, this paper proposed a fast computational method based on the advanced flexible multibody dynamics. By establishing an equivalent spring model to simplify the constraint conditions, the complicated constrained dynamics of catenary was transformed to the classical structural vibration solution, and the quality matrix and rigidity matrix were generated for the simplified system. The structural vibration modal of the flexible catenary was computed by using the MATLAB characteristic value computation function Eig. The proposed method was first applied to vibration of the classical simply supported beam. According to comparison between the computed results and corresponding theoretical solutions, the proposed method could accurately compute modal frequencies and vibration shapes of the simply supported beam. Moreover, the effect of the equivalent spring stiffness coefficient on the calculation results was analyzed. The results show the characteristic modal frequency can be computed accurately in the modal analysis of two kinds of catenaries. The proposal method provides a theoretical basis for further study on pantograph-catenary interaction dynamics.